Gendered occupational aspirations of boys and girls in Germany : the impact of local VET and labour markets - Malin, Lydia [Verfasser]; Jacob, Marita [Verfasser] (My University, 2019)
"Gender segregation in vocational education and training (VET) in different occupations is observed in many European countries. This occupational gender segregation depends on - among other factors - the initial occupational aspirations of adolescents. While previous research has mainly focused on individual-level explanations and on the family context, this study investigates the influence of local VET - and labour markets - on adolescent boys’ and girls’ occupational aspirations. More precisely, we look at: (1) the occupational structure of local VET and labour markets and (2) competition for VET opportunities. Using data from the German National Educational Panel Study of youth in grade 9 (age 15/16), we find that boys’ aspirations are oriented towards occupational opportunities in the local labour market and that they vary with competition. Girls’ aspirations are less likely to be gender-typical - neither female nor male - if there is low competition. However, with higher competition, girls also orient their aspirations towards occupational opportunities. Even if effect sizes of local context are small, we do find empirical evidence that contexts matter." (Author's abstract; BIBB-Doku)
Keywords: G 1.3.2.2.1 Erste Schwelle, in Ausbildung; G 1.3.1.1 Ausbildungsstellenmarkt; G 1.2 Arbeitsmarkt; G 2.4.5 Gender Mainstreaming; Berufswunsch; Berufsentscheidung; Ausbildungsstellenmarkt; Arbeitsmarkt; Geschlechtsspezifische Faktoren; Geschlechterverteilung; Nationales Bildungspanel